Sharing the Wealth:National Board Certified Teachers and the Students Who Need Them Most - Humphrey, Daniel C.; Koppich, Julia E.; Hough, Heather J. (Education Policy Analysis Archives, 2005)
It is a commonly understood problem in education that many highly qualified teachers tend to gravitate toward higher performing schools, including schools with lower minority enrollments and lower incidence of poverty. This article explores the distribution of a subset of teachers, namely, those who are National Board Certified. To what extent do these teachers' assignment choices mirror the pattern of their non-Board Certified colleagues and to what extent are they different? Part of a larger study of Board Certified Teachers in lower performing schools, the article examines the distribution of NBCTs in the six states with the largest number of them'California, Florida, Mississippi, North Carolina, Ohio, and South Carolina. The research finds that, with the exception of California, Board Certified Teachers are not equitably distributed across schools that serve different populations of students. In five of the six states examined, poor, minority, and lower performing students are far less likely to benefit from the teaching of an NBCT than are their more affluent, majority, higher performing peers. The article explores some possible explanations for the California distribution pattern as well as the kinds of incentives provided across the states for teachers to seek Board Certification and for those who earn it. The authors conclude with a rationale and a set of policy suggestions for realigning the distribution of NBCTs.